A Case of Sporadic Pseudohypoparathyroidism Type 1B Presented with Hypokalemia - Yang, Wen-jun; Zhang, Qin; Jin, Ping (Hormone and Metabolic Research, 2021)
Luo et al. 1 reported two cases of autosomal dominant pseudohypoparathyroidism type 1B (AD-PHP1B) and reviewed literature about the genetic and epigenetic characteristics of AD-PHP1B. Pseudohypoparathyroidism (PHP) is a cluster of heterogeneous diseases characterized by hypocalcemia and hyperphosphatemia due to resistance to parathyroid hormone (PTH). PHP1B almost results from methylation abnormalities of the maternal differentially methylated regions (DMRs) and can be divided into sporadic PHP1B and AD-PHP1B 1. As mentioned in this article 1, AD-PHP1B is caused by heterozygous maternal deletions within GNAS or STX16, which are associated with loss of methylation at the A/B DMR alone or at all maternally methylated GNAS exons. While sporadic PHP1B remains unclear at the molecular level, except for approximately 10% of the patients caused by paternal uniparental isodisomy or heterodisomy involving chromosome 20q (patUPD20q) 2. Here, we would like to present a rare case of sporadic PHP1B occurring in association with hypokalemia.